2006
DOI: 10.2298/tam0602123k
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chemical reaction, heat and mass transfer on boundary layer flow over a porous wedge with heat radiation in the presence of suction or injection

Abstract: The effect of chemical reaction, heat and mass transfer on boundary layer flow over a porous wedge with heat radiation has been studied in the presence of suction or injection. An approximate numerical solution for the steady laminar boundary-layer flow over a wall of the wedge in the presence of species concentration and mass diffusion has been obtained by solving the governing equations using numerical technique. The fluid is assumed to be viscous and incompressible. Numerical calculations are carried out fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 15 publications
(21 reference statements)
1
23
0
Order By: Relevance
“…Considerable literature can be found over combined heat and mass transfer in free convection boundary layer flow over heated surfaces along different geometries. Few researchers (e.g., Gebhart et al, 1989;Kandasamy et al, 2006;Chaudhary et al, 2006), investigated the impact of radiation on heat transfer in MHD mixed convection flow with viscous dissipation and ohmic heating effects. A problem of analytical conjugate phenomena of heat and mass transfer was examined by Noor et al (2012).…”
Section: Introductionmentioning
confidence: 99%
“…Considerable literature can be found over combined heat and mass transfer in free convection boundary layer flow over heated surfaces along different geometries. Few researchers (e.g., Gebhart et al, 1989;Kandasamy et al, 2006;Chaudhary et al, 2006), investigated the impact of radiation on heat transfer in MHD mixed convection flow with viscous dissipation and ohmic heating effects. A problem of analytical conjugate phenomena of heat and mass transfer was examined by Noor et al (2012).…”
Section: Introductionmentioning
confidence: 99%
“…A systematic simulation for the mass transfer effect on the two-dimensional unsteady MHD free convective flow past a vertical porous plate with variable suction were investigated by Ramana Kumari et al [13]. Kandasamy et al [6] reported the effects of thermal and mass transfer diffusion in MHD mixed convective flow over a porous wedge with heat radiation and considering suction/injection. The hydromagnetic unsteady mixed convection flow past porous plate sop in porous media was studied by Sharma et al [16].…”
Section: Introductionmentioning
confidence: 99%
“…Bhuvaneswari et al [8] have explained exact analysis of radiation convective heat and mass transfer flow over an inclined plate in a porous medium. Kandasamy and Devi [9] have presented the effects of chemical reaction, heat and mass transfer on non-linear laminar boundary-layer flow over a wedge with suction or injection. Prakash and Ogulu [11] have discussed the unsteady two-dimensional flow of a radiating and chemically reacting fluid with time dependent suction.…”
Section: Introductionmentioning
confidence: 99%